Kajian Kitab Manhaju Syawi dalam Membentuk Karakter Islami dan Spiritualisme Santri: Studi di Pondok Pesantren Putri Lirboyo H.M Al-Mahrusiyah I Kota Kediri - Muayanah, Nana; Zahid, Reza Ahmad (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This research is a form of obtaining knowledge related to the learning system of the Manhaju Syawi Book. It influences the formation of Islamic character and spiritualism of students at the Islamic Boarding School for Women Lirboyo H.M al-Mahrusiyah I Kediri City. The method is mixed methods (quantitative-qualitative) with a population used as a sample of 150 women students to analyze quantitative research data using a simple linear regression analysis formula. At the same time, the qualitative analysis uses descriptive qualitative data. The results showed several learning systems: bandongan, lecture question, and answer, sorogan, and demonstration. Quantitative data shows the influence of the study of Manhaju Syawi Book on the Islamic character building and formation of students' spiritualism, especially in instilling religious attitudes and spiritualism.